Using the Object Mapping Approach from Analysis to Implementation for Developing Student Registration System - Dhafer AbdulAmeer AbdulMonim; zainab hassan Muhamad; Bashar Alathari (Institute of Advanced Engineering and Science, 2019)
The Unified Modeling Language (UML) is the effective standard language of an object-oriented based system analysis and design. The using of object-oriented approach based on UML specification can offer an understandable model, which can reduce the system's complexity. The use-case diagram, class diagram and sequence diagram are important models of the system development during early stages. The object mapping approach between UML class diagram in the analysis phase and source code in the implementation phase is a significant process in the software development life cycle. In order to ensure the consistency of system requirements from analysis to implementation. This paper presents the student registration system by using object mapping based on UML. The UML specification and the generation of Java source code influenced by specific features of class in object-oriented such as inheritance and the association between the classes.